Effect of Films Thickness on the Properties of ITO Thin Films Prepared by Electron Beam Evaporation - Artorn Pokaipisit; Mati Horprathum; Pichet Limsuwan (Agriculture and Natural Resources, 2007)
Indium tin oxide (ITO) thin films were prepared on glass slide substrates at various thicknesses by electron beam evaporation (e-beam) from a tablet of In2O3 and SnO2 (9:1). The ITO thin films were fabricated at substrate temperatures of 150 °C, deposition rate of 2 Å/s and oxygen flow rate of 12 sccm. The structure, surface morphology, electrical and optical properties of ITO thin films were investigated. The structure and surface morphology of films were monitored by using X–ray diffraction (XRD) and atomic force microscopy (AFM), respectively. The optical transmittance and sheet resistance of ITO thin films were measured by spectrophotometer and four-point probe. It was found that transmittance and sheet resistance of ITO thin films on glass slide decreased as film thickness increased from 200 nm to 700 nm. The transmittance spectra in the visible region (400-700 nm) and the sheet resistance decreased from 76.63% to 57.89% and from 16 Ω/sq. to 4 Ω/sq., respectively, with increasing the films thickness.